2022
DOI: 10.30919/es8e624
|View full text |Cite
|
Sign up to set email alerts
|

On the Arbitrariness and Complexity in Thermoeconomics due to Waste Cost and Supplementary Firing Treatment

Abstract: Cost allocation, optimization, and diagnosis are the main application fields of thermoeconomics. Cost allocation allows evaluating the plant cost formation process. For plants containing dissipative equipment, the use of total exergy flows in the conventional productive diagrams is not able to isolate these components. The physical exergy disaggregation, despite increases the complexity, allows the treatment of dissipative equipment and residues. Nevertheless, conventional productive diagrams based on producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
2
0
3
Order By: Relevance
“…A Figura 6 representa um sistema de cogeração genérico em que a partir de um combustível (EC) são gerados dois produtos (PL e QU), assim como é o caso do sistema com turbina a gás da Figura 1. Ao aplicar o balanço de custo da Equação (1) nesse sistema genérico, obtém-se a Equação (11), em que 𝑐 𝑃 𝐿 e 𝑐 𝑄 𝑈 são os custos unitários monetários dos produtos finais. ), e por isso também deslocaria a reta inicial para retas paralelas em comparação com a condição inicial.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…A Figura 6 representa um sistema de cogeração genérico em que a partir de um combustível (EC) são gerados dois produtos (PL e QU), assim como é o caso do sistema com turbina a gás da Figura 1. Ao aplicar o balanço de custo da Equação (1) nesse sistema genérico, obtém-se a Equação (11), em que 𝑐 𝑃 𝐿 e 𝑐 𝑄 𝑈 são os custos unitários monetários dos produtos finais. ), e por isso também deslocaria a reta inicial para retas paralelas em comparação com a condição inicial.…”
Section: Resultsunclassified
“…Segundo esse critério, todos os produtos de um subsistema tem o mesmo custo unitário pois foram gerados no mesmo processo produtivo sob as mesmas irreversibilidades. No caso dos diagramas físico ou abrangente [11], utiliza-se as regras do insumo e do produto [15]. A primeira considera que um componente utiliza uma parte da exergia do fluxo de entrada para produzir um dado produto e que a parte restante da exergia do fluxo de entrada tem o mesmo custo unitário do fluxo de entrada.…”
Section: Modelagem Termoeconômicaunclassified
See 1 more Smart Citation
“…Multiproduct is the method used to formulate the auxiliary equation in each bifurcation. This method assumes that all productive flows exiting the same subsystem or unit have the same unit cost since they are exiting from the same subsystem with the same resources and irreversibilities [ 34 ].…”
Section: Case Studiesmentioning
confidence: 99%
“…In such scenarios, thermoeconomics enables a rational allocation (based on physical criteria) of monetary, exergetic, and environmental costs for these final products. Consequently, a comparison becomes feasible between the exergetic/monetary/environmental costs of each product and the production cost of each individual product in separate systems, as shown in papers assessing the exergetic unit cost (in a regenerative gas turbine cogeneration system [13]; in a cogeneration system with gas turbine, intercooler, and supplementary firing [14]; and in a combined cycle [15]), monetary unit cost (in a gas turbine cogeneration system [16] and in a power generation system of a steel mill plant [17]), and emissions pollutant allocation (in gas and steam cogeneration systems [18], in a gas cogeneration system with supplementary firing [19], in a combined cycle [20], and in a dual product heat pump [21]). Despite the practical relevance of this aspect, in the literature review, no studies were found that dealt with the incorporation and internalization of the monetary unit cost linked to the carbon market in the thermoeconomic evaluations of multi-product plants.…”
Section: Introductionmentioning
confidence: 99%